CALOTRITON: a convective boundary layer height estimation algorithm from ultra-high-frequency (UHF) wind profiler data - Philibert, Alban; Lothon, Marie; Amestoy, Julien; Meslin, Pierre-Yves; Derrien, Solène; Bezombes, Yannick; Campistron, Bernard; Lohou, Fabienne; Vial, Antoine; Canut-Rocafort, Guylaine; Reuder, Joachim; Brooke, Jennifer K. (Atmospheric measurement techniques, 2024)
Long time series of observations of atmospheric dynamics and composition are collected at the French Pyrenean Platform for Observation of the Atmosphere (P2OA). Planetary boundary layer depth is a key variable of the climate system, but it remains difficult to estimate and analyse statistically. In order to obtain reliable estimates of the convective boundary layer height (Zi) and to allow long-term series analyses, a new restitution algorithm, named CALOTRITON, has been developed. It is based on the observations of an ultra-high-frequency (UHF) radar wind profiler (RWP) from P2OA with the help of other instruments for evaluation. Estimates of Zi are based on the principle that the top of the convective boundary layer is associated with both a marked inversion and a decrease in turbulence. Those two criteria are respectively manifested by larger RWP reflectivity and smaller vertical-velocity Doppler spectral width. With this in mind, we introduce a new UHF-deduced dimensionless parameter which weighs the air refractive index structure coefficient with the inverse of vertical velocity standard deviation to the power of x. We then search for the most appropriate local maxima of this parameter for Zi estimates with defined criteria and constraints such as temporal continuity. Given that Zi should correspond to fair-weather cloud base height, we use ceilometer data to optimize our choice of the power x and find that x=3 provides the best comparisons. The estimates of Zi by CALOTRITON are evaluated using different Zi estimates deduced from radiosounding according to different definitions. The comparison shows excellent results with a regression coefficient of up to 0.96 and a root-mean-square error of 71 m, which is close to the vertical resolution of the UHF RWP of 75 m, when conditions are optimal. In more complex situations, that is when the atmospheric vertical structure is itself particularly ambiguous, secondary retrievals allow us to identify potential thermal internal boundary layers or residual layers and help to qualify the Zi estimations. Frequent estimate errors are observed nevertheless; for example, when Zi is below the UHF RWP first reliable gate or when the boundary layer begins its transition to a stable nocturnal boundary layer.